USE OF INSTAGRAM SOCIAL MEDIA BY JABODEBEK LRT PUBLIC RELATIONS AS INFORMATION MEDIA FOR THE COMMUNITY - Faaroek, Safiani A.; Sayidah, Umm (Jurnal Review Pendidikan dan Pengajaran, 2024)
Instagram is a social media application whose users are increasing to the point where it occupies the second most frequently used social media position. This makes Jabodebek LRT use Instagram to spread an information. LRT Jabodebek is one of the transportation companies that has been using Instagram since 2016. By using Instagram as a medium of information to the public, it's able to make people aware of information about LRT Jabodebek and get a good response from the public. The purpose of this research is to find out how Public Relations of LRT Jabodebek utilizes social media Instagram to provide information to the public. The subject of this research is the public relations of LRT Jabodebek , while the research object is Instagram @Lrt_Jabodebek. The method in this research is a qualitative method with a case study type of research and uses diffusion of innovation theory developed by Everett Rogers. The key informants in this research are (1) Public Relations officer of LRT Jabodebek (2) Public Relations Expert of LRT Jabodebek . For the supporting informants in this research are two followers of Instagram @Lrt_Jabodebek. The results of this research are in using Instagram social media as an information medium for the public, LRT Jabodebek through the innovation diffusion stage in producing information content until the public likes it.